ANALISIS KITAB SYARAḤ SUNAN ABĪ DĀUD LIBNI ROSLĀN KARYA SHIHĀB AL-DĪN AL- ‘ABBĀS MUḤAMMAD BIN ḤUSAIN BIN ‘ALĪ BIN ROSLĀN AL-MAQDISĪ AL-ROMLĪ AL- SYAFI’Ī (W. 844 H) - Abdurrohman Abdurrohman (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
Muslims have two main guidelines, namely al-Qur'an and al-Hadis. The Qur'an is the word of God revealed to the Prophet Muhammad PBUH through the angel Gabriel, aiming to provide guidance for safety and happiness in the world and the hereafter. hadith is very urgent to understand and know, so many scholars have compiled hadith books and also hadith briefings as reinforcement of the hadith. Ibn Raslān's Sahīh Sunan Abī Dāud Libni Roslān is one such book. This article will examine the method and systematization of the book. After the author analyzed this book, the author found several advantages that were not found in the previous books, including: 1) This book explains more about the identity of the author. 2) This book also explains the identity of the book that is syarah, namely the Sunān Abī Dāud. 3) Including a complete series of sanads.